Molecular characterisation of a turbot Mx cDNA - Abollo, Elvira; Ordás, M. Camino; Dios, S.; Figueras Huerta, Antonio; Novoa, Beatriz (Fish & Shellfish Immunology, 2005)
6 páginas, 3 figuras This research has been supported by a Marie Curie Fellowship of the European Community Fifth Framework Programme under contract number QLK5-CT-2002-51499, and by the Ministerio de Ciencia y Tecnología under project BIO2001 2324-C02. Peer reviewed